Effect of Dog Presence on Stress Levels in Students under Psychological Strain: A Pilot Study - Machová, Kristýna; Procházková, Radka; Vadroňová, Mariana; Součková, Michaela; Prouzová, Eliška (International journal of environmental research and public health, 2020)
As university students face many stressful situations, especially during the examination period, this study focused on the use of animal-assisted activities (AAAs) with a dog as a means of relieving students' stress before a final exam. The aim was to determine whether a 10-min interaction with a dog affected subjectively evaluated stress and mood, objective blood pressure, and heart rate. Ninety-three female students (mean age = 22.5 years; standard deviation = 3.8 years) were divided into three groups according to their preference. The first group underwent AAAs (n = 26), the second group chose a relaxation technique (n = 28), and the last one was a control group (n = 39). Physiological values were measured using a pressure gauge and the subjective feelings of stress and mood were evaluated by the Likert scale 1-5. The AAA group showed significant improvement after 10 min of interaction in both mood and stress, with no change in heart rate and blood pressure. The remaining groups showed a significant decrease in blood pressure, but not in heart rate, with different evaluations of mood and stress. AAAs with a dog appear to be effective in improving students' mood and stress without affecting their physiological parameters.
Keywords: Relaxation Therapy; dospělí; Animals; Students; Female; dog; stress; Adult; mladý dospělý; ženské pohlaví; psychický stres; lidé; Pilot Projects; Affect; pilotní projekty; Dogs; afekt; krevní tlak; srdeční frekvence; Young Adult; animal assisted activity; students’ health; Animal Assisted Therapy; zooterapie; relaxační terapie; studenti; zvířata; Blood Pressure; Heart Rate; Stress, Psychological; psi; Humans